Fatigue and impact properties of kenaf/glass-reinforced hybrid pultruded composites for structural applications - Balakrishnan, Thinesh Sharma; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Basri, Adi Azriff; Shah, Ain Umaira Md; Sebaey, Tamer Ali; Łukaszewicz, Andrzej; Józwik, Jerzy; Grzejda, Rafał (Multidisciplinary Digital Publishing Institute, 2024)
To address the weight, cost, and sustainability associated with fibreglass application in structural composites, plant fibres serve as an alternative to reduce and replace the usage of glass fibres. However, there remains a gap in the comprehensive research on plant fibre composites, particularly in their durability for viable structural applications. This research investigates the fatigue and impact properties of pultruded kenaf/glass-reinforced hybrid polyester composites tailored for structural applications. Utilising kenaf fibres in mat form, unidirectional E-glass fibre direct roving yarns, and unsaturated polyester resin as key constituents, pultruded kenaf/glass hybrid profiles were fabricated. The study reveals that pultruded WK/UG alternate specimens exhibit commendable fatigue properties (18,630 cycles at 60% ultimate tensile strength, UTS) and fracture energy (261.3 kJ/m2), showcasing promise for moderate load structural applications. Notably, the pultruded 3 WK/UG/3WK variant emerges as a viable contender for low-load structural tasks recorded satisfactory fatigue properties (10,730 cycles at 60% UTS) and fracture energy (167.09 kJ/m2). Fatigue failure modes indicate that the stress applied is evenly distributed. Ductile failures and delaminations during impact test can be attributed to damping and energy absorbing properties of kenaf fibres. Moreover, incorporating kenaf as a hybrid alternative demonstrates substantial reductions in cost (35.7–50%) and weight (9.6–19.1%). This research establishes a foundation for advancing sustainable and efficient structural materials and highlights the significant role of materials design in shaping the future of engineering applications.